Factors Affecting Firm Value with Market Risk as a Moderating Variable - Indah Lia Puspita; Eka Sariningsih; Filiya Wulandari (LPPM Institut Pendidikan Nusantara Global, 2026)
Firm value is a key indicator of a company’s ability to create shareholder wealth and attract investors. This study examines the effects of Corporate Social Responsibility (CSR), Good Corporate Governance (GCG), Intellectual Capital Disclosure (ICD), and Corporate Reputation on Firm Value, with Market Risk as a moderating variable. The study focuses on food and beverage manufacturing firms listed on the Indonesia Stock Exchange (IDX) during 2021–2024. A quantitative approach was employed using secondary data from annual reports, audited financial statements, and sustainability reports. The sample consisted of 27 firms, yielding 108 firm-year observations selected through purposive sampling. Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with IBM SPSS Statistics 26. The results indicate that CSR (β = 0.324; p = 0.011), GCG (β = 0.287; p = 0.018), and Corporate Reputation (β = 0.456; p = 0.001) have significant positive effects on Firm Value, while ICD has a positive but insignificant effect (β = 0.198; p = 0.063). Market Risk significantly moderates the relationship between Corporate Reputation and Firm Value (β = 0.287; p = 0.017), increasing the model’s Adjusted R² from 39.1% to 42.2%. The model’s R² is 0.427, indicating that the independent variables explain 42.7% of the variation in Firm Value.